Criminalistic Aspects of Engagement of the Undercover Agent - Moravac, Siniša (Kriminalističke teme, 2019)
Reason for writing and research problem(s): One of the basic requirements of successful and relatively harmonious functioning of every society is the suppression of criminality. As a necessity, there is also the need for engaging a undercover agent. Engaging a undercover agent involves a wide range of time-coordinated activities. For this reason, the paper analyzes the activities that are based on the selection of a person who will be engaged as a undercover agent, through his actions in an organized criminal group, to the interruption of the task and his "pulling out" from the milieu he was in. Aims of the paper (scientific and/ or social): The most important goal of the paper that is trying to achieve is to point out the correct and comprehensive overview of the essence of the criminalistic aspects of the engagement of the undercover agent, bearing in mind the inescapable importance and complexity of the subject in matter. In this way, the work should provide some practical and very useful recommendations for the treatment of persons engaged in the capacity of a undercover agent. Also, the analysis and criticism of certain theoretical aspects of the subject of this paper should lead to the resolution of certain theoretical problems and illogicality. Methodology/Design: Methodologically, the author used analysis, synthesis, abstraction, general theoretical approach, and to a certain extent generalization, of course to the extent that generalization is acceptable when it comes to the subject matter of the paper. A large part of the exposition in the paper is of a descriptive character. More precisely speaking, describing possible practical situations is in the function of easier understanding of the essence of the topic. Theoretical analyzes are given only to individual classifications and analysis of the perception of certain authors on certain issues. Research/Paper limitation: The basic limitation of paper is that the paper is the result of purely theoretical reflections and analysis of author based on theoretical perceptions and attitudes, on the one hand, and practical experiences of individuals who were engaged as a undercover agent on the other. Therefore, the limitation is reflected in the fact that the author of this paper has no practical experience in this regard which could qualitatively considerably contribute to the work. One limitation of his paper is also reflected in the impossibility of achieving a greater degree of generalization of given recommendations, which is a consequence of a marked differentiation of practice. Results/Findings: On the base of the analysis made, a rather broad overview of the criminalistic aspects of engaging a undercover agent, in all its phases, was offered. Also, the presence of certain classification and terminological problems and inconsistencies was determined. In that sense, it was pointed out the possible solution to the problem. The work of the undercover agent is very diverse. This is due to the marked heterogeneity of the manifestations of criminal activities. This heterogeneity makes the involvement of a undercover agent to a great extent unpredictable. General conclusion: Engagement of a undercover agent is a very complex activity whose success depends directly on many factors of a different nature. Certain classifications represented and common in theory and used terminology are not quite appropriate, or they do not always correspond to the essence of things. The pursuit of engaging a undercover agent is indisputable, and such is the need for scientific analysis, which is reflected in giving recommendations and guidelines for practical treatment. Research/paper validity: The imminent need to suppress organized crime and the specificity of its suppression, and above all this includes the difficulties of suppression, undeniably justify and form the essence of the analysis of the subject of this paper. Furthermore, the work should also point to the complexity and difficulties that inevitably occur in the entire process of engaging a undercover agent. The above is valid for persons who in this capacity can be engaged and the support team, but also for the public, who should properly understand what is the essence of engaging a undercover agent.